2021
DOI: 10.1007/s12063-021-00203-1
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain sustainability during turbulent environment: Examining the role of firm capabilities and government regulation

Abstract: The turbulent environment like COVID-19 has forced many firms to the brink of collapse. It has a devastating impact on the supply chain management and its sustainability. Many firms were forced to close due to unavailability of raw materials, essential ingredients, and labor shortage. Not many firms were capable of efficiently handling such disruptive situation. There is not much study on appropriate supply chain strategy for such turbulent situation. The practitioners as well as academic researchers are inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 94 publications
2
36
0
1
Order By: Relevance
“…This has become more critical with the increasing environmental turbulence that is experienced in the operating environment. Chatterjee and Chaudhuri (2021) highlighted such turbulence, which includes market turbulence, competitive intensity, technological turbulence and pandemic turbulence. Fundin et al (2020) reported that stability in change forms a component of the Quality 2030 agenda.…”
Section: Knowledge For Decision-making and Future Predictionmentioning
confidence: 99%
“…This has become more critical with the increasing environmental turbulence that is experienced in the operating environment. Chatterjee and Chaudhuri (2021) highlighted such turbulence, which includes market turbulence, competitive intensity, technological turbulence and pandemic turbulence. Fundin et al (2020) reported that stability in change forms a component of the Quality 2030 agenda.…”
Section: Knowledge For Decision-making and Future Predictionmentioning
confidence: 99%
“…However, there are studies that do not associate disruptions with resilience. Thereby, different concepts from the perspective of disruptions were studied such as response to global economic recession (Al-Mansour and Al-Ajmi, 2020), major issues and responses (Sharma, Adhikary, and Borah, 2020), validity of existing supply chain disruption philosophies in COVID-19 (Sinha, et al, 2020), failure probability (Starita and Paola Scaparra, 2021), sustainability during turbulent situation (Chatterjee and Chaudhuri, 2021), forward and backward disruption propagation (Li, Chen, et al, 2021), and optimizing pricing and sourcing decisions (Gupta, et al, 2021). Furthermore, concepts like ambidexterity (Wang, Yan, et al, 2021), artificial intelligence (Modgil, et al, 2021), regionalization (Pla-Barber, et al, 2021), and resiliency strategies (Chowdhury, et al, 2020) were researched from the perspective of resiliency.…”
Section: Supply Chain Managementmentioning
confidence: 99%
“…Moreover, sustainability has also been researched frequently in strategic management literature during the pandemic. In this sense, sustainability of certain industries like the hospitality industry, clothing and textile (Jones and Comfort, 2020;Zhao and Kim, 2021), sustainable development goals (van Zanten and van Tulder, 2020), employment (Lopez-Cabrales and DeNisi, 2021), sustainability in SMEs (Amoah, et al 2021;González-Díaz, et al, 2021), and determinants of sustainability (Chatterjee and Chaudhuri, 2021) was examined. In addition to organizational competencies, organizational incompetencies was examined during-COVID-19 as well.…”
Section: Competenciesmentioning
confidence: 99%
“…In their study of new product development, Danneels and Sethi ( 2011 ) used three scales for the customer turbulence, competitive turbulence, and technological turbulence faced by U.S. manufacturing firms. Other researchers continue to adapt measurement scales for environmental turbulence according to their needs (Chatterjee and Chaudhuri 2021 ; Lichtenthaler 2009 ; Sethi and Iqbal 2008 ; Zhou et al 2019 ).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%